Effect of in ovo feeding of L-glutamine + ISP to chick embryos - Rufino, João Paulo Ferreira; Cruz, Frank George Guimarães; Costa, Valcely da Rocha; Silva, André Ferreira; Oliveira Filho, Pedro Alves de; Melo, Lucas Duque; Bezerra, Natalia dos Santos (Medicina Veterinária, 2020)
In ovo feeding (IOF) is the biotechnology that injects nutrients into the amnion of the avian embryo may cause an increase in hatchability and gastrointestinal development, and affecting the serum metabolism. This hypothesis was evaluated using 5 IOF solutions containing L-glutamine and L-glutamine + ISP (Isolated Soy Protein). 300 fertile eggs Rhode Island Red (breeders with 43-weeks) were distributed in a completely randomized experimental design with the treatments constituted by two controls (intact egg and IOF control with saline solution) and three solutions containing L-glutamine and L-glutamine + ISP, with 60 replicates (eggs) each. Data collected were subjected to the Tukey test at 5% of significance. There was a significantly lower (p<0.01) in hatchability from the IOF of L-glutamine + ISP, and a consequent increase in the intermediary embryo mortality. The yolk sac was higher (p<0.01) in chicks subjected to solutions containing 0.5% L-glutamine and 0.5% L-glutamine + 1.0% ISP, whereas all in ovo embryos presented great (p<0.05) development of heart and pancreas than intact eggs. In ovo fed embryos at 0.5% L-glutamine and 0.5% L-glutamine + 1.0% ISP presented great developed of gastrointestinal tract than intact eggs. In conclusion, the results of this study indicated that 0.5% L-glutamine may be used to IOF in chick embryos without a negative influence on chick weight and gastrointestinal tract development, acting as a metabolism regulator and obtaining better hatchability.